2017
DOI: 10.3389/fgene.2017.00189
|View full text |Cite
|
Sign up to set email alerts
|

Post-transcriptional Regulation of PCSK9 by miR-191, miR-222, and miR-224

Abstract: Since proprotein convertase subtilisin kexin 9 (PCSK9) discovery, a gene involved in LDL metabolism regulation and cardiovascular diseases (CVD), many therapeutic strategies have been introduced for direct targeting of PCSK9. The main goal of these strategies has been to reduce PCSK9 protein level either by application of antibodies or inhibition of its production. In this study, we have tried to discover microRNAs (miRNAs) which can target, and hence regulate, PCSK9 expression. Using bioinformatics tools, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 42 publications
1
42
0
1
Order By: Relevance
“…Based on previous studies, there are miR-222-binding sites in PCSK9 , 15 MIA3 , 16 ABCG2 , 17 PUMA , 18 DKK2 , 19 and Pten . 20 To further evaluate it in the present study, miR-222 mimic or negative control (NC) mimic was transfected into 293A cells.…”
Section: Resultsmentioning
confidence: 92%
“…Based on previous studies, there are miR-222-binding sites in PCSK9 , 15 MIA3 , 16 ABCG2 , 17 PUMA , 18 DKK2 , 19 and Pten . 20 To further evaluate it in the present study, miR-222 mimic or negative control (NC) mimic was transfected into 293A cells.…”
Section: Resultsmentioning
confidence: 92%
“…Fortunately, many studies have been performed to find their associated up/downstream mRNAs and antisense mRNAs related to lncRNAs. Functional annotation and enrichment are considered an effective way to reveal the biological significance and biological processes or functions of most enriched genes [28][29][30]. In this study, based on these basic principles, 2046 genes were scanned as apcGenes and antisense mRNAs for 883 lncRNAs, combined with the differentially expressed lncRNA, mRNAs and predicted pre-miRNA, as well as their interaction, and 1478 genes were detected and further served for GO enrichment and KEGG pathway analyses.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, CD105+ EVs could probably promote vascular regeneration, either through a specific interaction or through miRNA delivering into recipient cells. Indeed, it has been found that CD105+ EVs-carried miRNA-222 may contribute to weaken inflammatory effects modulating the endothelial expression of ICAM-1 [47], as well as for the PCSK9 protein, which has been related as a biomarker for different cardiovascular negative conditions [48].…”
Section: Discussionmentioning
confidence: 99%